The more and the heavier may not always be an answer - Pyo, Hongryull; Lee, Se-Hoon; Kim, Jhingook (Journal of Thoracic Disease, 2018)
Non-small cell lung cancer (NSCLC), especially locally advanced NSCLC, is difficult to treat. As patients with locally advanced NSCLC present no evidence of systemic spread, cure is suggested as the treatment goal. However, treatment outcomes are often unsatisfactory.